1897 S.C. Acts 423, no. 251, § 1 - (:unkn) unknown (My University, 1897)
Prohibited the concealed carry of a pistol, dirk, dagger, slingshot, metal knuckles, razor, or other deadly weapon usually used for the infliction of personal injury. Violators fined not more than one hundred dollars and not less than twenty dollars, or imprisoned not more than thirty nor less than days.
Keywords: CARRY - CONCEALED